Analisis Pengaruh BI Rate dan Jumlah Uang Beredar (M2) Terhadap Kurs Dolar AS atas Rupiah di Indonesia Tahun 2005-2021 - Fitry Magdalena; Any Widayatsari; Darmayuda Darmayuda (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2023)
This study aims to determine and analyze the effect of BI rate and money supply on the US dolar exchange rate against the rupiah in Indonesia for the period 2005-2021. The method used in this research is descriptive and quantitative methods of correlation type. The data used in this study are secondary time series data provided by Bank Indonesia. Data collection techniques using documentation. Analysis of the data used is multiple linear regression with the Error Correction Model (ECM) with processing using E-views versi 10. the result of this study in the long run BI rate and money supply have a positive effect on the dolar exchange rate againts rupiah. in the short term, BI rate has a positive effect. money supply has no effect on the dolar exchange rate againts the rupiah.